NILAI-NILAI SOSIAL DALAM NOVEL HUJAN KARYA TERE LIYE SEBAGAI BAHAN PEMBELAJARAN KAJIAN PROSA PADA MAHASISWA PROGRAM STUDI DIKSATRASIADA UNIVERSITAS MATHLA’UL ANWAR BANTEN - Sopyan Sauri (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2020)
ABSTRACT: The purpose of this study is to describe the social values contained in the rainy novel by Tere Liye. The research method used in studying the rain novel by Tere Liye is a descriptive qualitative method. The object of this research is the social values in the rainy novel by Tere Liye published by PT Gramedia Main Library of 2016. The technique of collecting data in this study uses literature study techniques. The data analysis technique uses the semiotic model reading method, heuristic and hermeneutic reading.The results of data analysis on the rainy novel by Tere Liye can be concluded that the social values contained in the novel are the value of helping, family, loyalty, caring, responsibility, discipline, empathy, harmony of life, tolerance, cooperation, and democracy.The results of the analysis of social values in the rain novel by Tere Liye can be used as an alternative material for prose study in Indonesian literary language education students and the Mathla'ul anwar University Banten area